2012
DOI: 10.1016/j.jvs.2011.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular vs open repair for ruptured abdominal aortic aneurysm

Abstract: Objective Endovascular repair (EVAR) of ruptured abdominal aortic aneurysm (rAAA) has become first-line therapy at our institution and is performed under a standardized protocol. We compare perioperative mortality, midterm survival, and morbidity after EVAR and open surgical repair (OSR). Methods Records were retrospectively reviewed from May 2000 to September 2010 for repair of infrarenal rAAAs. Primary end points included perioperative mortality and midterm survival. Secondary end points included acute lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 28 publications
3
33
0
1
Order By: Relevance
“…EVAR and open surgical aneurysm repair are the predominant surgical methods used in the acute setting for a ruptured aortic aneurysm, with EVAR currently being preferred due to some studies suggesting a lower perioperative morbidity and mortality, although as stated previously some studies also refute this 21, 22 . We found that patients admitted on the weekdays and weekends for ruptured AAA had similar rates of EVAR and open repair while the difference was significant in TAA.…”
Section: Discussionmentioning
confidence: 96%
“…EVAR and open surgical aneurysm repair are the predominant surgical methods used in the acute setting for a ruptured aortic aneurysm, with EVAR currently being preferred due to some studies suggesting a lower perioperative morbidity and mortality, although as stated previously some studies also refute this 21, 22 . We found that patients admitted on the weekdays and weekends for ruptured AAA had similar rates of EVAR and open repair while the difference was significant in TAA.…”
Section: Discussionmentioning
confidence: 96%
“…11,12 EVAR is characterized by slight trauma, which avoids great pain and anguish brought by traditional surgery, reduces the incidence of complications and mortality of patient heart, lungs, and other vital organs, especially provides treatment opportunities for patients who are with serious complications and cannot be expected to tolerate traditional OSR. 13,14 OSR has long been a standard treatment for ruptured AAA. 15 It is usually performed under general anesthesia to take abdominal incision, layer by layer separation of soft tissue to show AAA proximal and distal aneurysm neck and expose AAA.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first published report of EVAR for rAAA (rEVAR) in 1994 [10], several studies have demonstrated its feasibility and a strong correlation between rEVAR and improved 30-day mortality outcomes compared with OR [11,12]. Although several case series have demonstrated reduction in mortality and morbidity with rEVAR compared with OR, most of the data are few, retrospectively evaluated, and limited by bias in the selection of patients [13].…”
Section: Introductionmentioning
confidence: 99%